MENILIK KEDUDUKAN PTUN SEBAGAI GARDA KEADILAN ADMINISTRATIF DALAM MENJAGA KUALITAS DEMOKRASI INDONESIA - Timbo Mangaranap Sirait; Khalimi; Lisno Setiawan (The Juris, 2025)
The Administrative Court (PTUN) plays a crucial role as the last resort for justice seekers after exhausting avenues of Objection and Administrative Appeal, particularly in safeguarding the quality of democracy in Indonesia. As an institution that oversees state administrative actions, the PTUN has the authority to adjudicate disputes between citizens and the government. In recent years, the PTUN has issued various rulings that reinforce democratic principles such as freedom of expression and broader political access. This analysis employs a normative juridical method through literature review and case studies of PTUN decisions, aiming to identify and evaluate the PTUN’s contribution in administratively maintaining and supervising the quality of democracy in Indonesia. The research addresses the following issues: (a) How does the PTUN contribute to maintaining the quality of democracy in Indonesia? and (b) How does the PTUN ensure transparency and accountability in government? In conclusion, first, based on the analysis of several decisions, the PTUN plays a significant role and serves as a front-line guardian in maintaining and overseeing the quality of democracy in Indonesia through its rulings. Second, the PTUN has upheld judicial neutrality, the integrity of electoral processes, and has ensured transparency and accountability in the administration of government.